2011
DOI: 10.1016/j.enpol.2011.01.002
|View full text |Cite
|
Sign up to set email alerts
|

Exploration of resource and transmission expansion decisions in the Western Renewable Energy Zone initiative

Abstract: Building transmission to reach renewable energy (RE) goals requires coordination among renewable developers, utilities and transmission owners, resource and transmission planners, state and federal regulators, and environmental organizations. The Western Renewable Energy Zone (WREZ) initiative brings together a diverse set of voices to develop data, tools, and a unique forum for coordinating transmission expansion in the Western Interconnection. In this report we use a new tool developed in the WREZ initiative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(9 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…However, basing costs on interconnection reports tends to neglect the costs of region-wide transmission investments. A study of the western United States found transmission costs of $9/MWh or $314/kW when considering the integration of wind, solar, geothermal, biomass, and hydro resources (Mills, Phadke, and Wiser 2011). Finally, a study of utility-scale wind and solar transmission costs found costs of $0.83-$75/MWh for proposed western U.S. projects, with wind transmission costs often at least $20/MWh (Kahn 2010;.…”
Section: Figure 1 Historical Transmission Constructionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, basing costs on interconnection reports tends to neglect the costs of region-wide transmission investments. A study of the western United States found transmission costs of $9/MWh or $314/kW when considering the integration of wind, solar, geothermal, biomass, and hydro resources (Mills, Phadke, and Wiser 2011). Finally, a study of utility-scale wind and solar transmission costs found costs of $0.83-$75/MWh for proposed western U.S. projects, with wind transmission costs often at least $20/MWh (Kahn 2010;.…”
Section: Figure 1 Historical Transmission Constructionmentioning
confidence: 99%
“…Numerous stakeholders support continued growth of cost-competitive VRE, and many researchers have studied the potential for high VRE penetrations on the electrical grid (Sørensen 2008;BNEF 2018;Elliston, Diesendorf, and MacGill 2012;Connolly et al 2011;Mathiesen, Lund, and Karlsson 2011;Lund and Mathiesen 2009;Liu et al 2011;Shoshanna 2011; . To make VRE investment decisions, policy and electric-sector decision makers face numerous tradeoffs related to location constraints, solar/wind resource potential, supporting infrastructure requirements, and so forth (Mills, Phadke, and Wiser 2011). Analysts typically incorporate these tradeoffs into project benefit calculations (estimates of VRE energy and capacity value) and project cost calculations (estimates of VRE integration costs such as supply-demand balancing and transmission investment) (Mills and Wiser 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Without the virtual load, the day-ahead * The load growth rate is based on a load forecast developed for WECC transmission planning studies and includes the impact of state and national efficiency programs. † Specifically, at 30% wind penetration, wind is procured from the WY_EA, WY_NO and WY_SO WREZ hubs based on the analysis in 35 . This analysis does not consider policy influences in wind siting decisions.…”
Section: Case Studymentioning
confidence: 99%
“…Here, the primary objective is neither to minimize the cost of the transmission investment, nor to maximize the market-based definition of social welfare, but to maximize the integration of wind generation into electricity markets while assessing the financial risk of the required transmission expansion/reinforcement. This way, the proposed model naturally yields an estimate of the amount of market-integrable wind resources at a given location and the resulting decision support tool may be very useful to conduct analysis complementary to those available in the technical literature, in which the economic potential of wind resources is appraised (see [15]- [17] and references therein). In these studies, however, crucial factors such as demand and wind uncertainty, load and wind correlation, investments costs and financial risk, market competition or network congestion are either accounted for based on estimates, not explicitly modeled, or just disregarded.…”
Section: Introductionmentioning
confidence: 99%